Menu pilihan diit nasi yang disajikan berpengaruh terhadap tingkat kepuasan pasien VIP di Rumah Sakit Umum Daerah Provinsi Sulawesi Tenggara - Sri Yunanci Gobel; R Dwi Budiningsari (Jurnal Gizi Klinik Indonesia, 2011)
Background: The provision of foods in hospitals often becomes a public concern, particularly in relation to patient satisfaction. This may be due to not only the psychological effect of sick ill people but also because foods as output of food provision does not often give satisfaction to the patient.Objective: To find out the effect of rice diet selective menu to satisfaction of VIP inpatients at local hospital of the Province of Sulawesi Tenggara.Method: A cross sectional study was conducted. Population of the study were VIP inpatiens; samples were patients that fulfilled inclusion and exclusion criteria in September-December 2008. Samples were purposively taken. Data analysis used bivariate with chi square and multivariate with logistic regression test.Result: Out of 49 patients that got selected menu and standard menu in aspect of food appearance as many as 45 (91.8%) were satisfied in selected menu and 31 (63.3%) were satisfied in standard menu; in aspect of food taste 44 (89.8%) were satisfied in selected menu and 23 (46.9%) were satisfied in standard menu; in aspect of food serving 47 (95.9%) were satisfied in selected menu and 40 (81.6%) were satisfied in standard menu.Conclusion: In aspect of appearance, color, shape and portion of foods significantly affected patient satisfaction whereas texture did not affect patient satisfaction. In aspect of taste, all variables affected patient satisfaction. In aspect of food serving all variables did not affect patient satisfaction.